When public managing fails. The housing question in Europe - Bussotti, L. (Problems of Management in the 21st Century, 2019)
If one seeks to rent a house for spending some months in a European city, or just some days on holiday, an aspect becomes immediately clear: the quasi-monopoly of an on-line platform, which proposes interesting and innovative solutions, from an entire apartment to a single room. This on-line platform is Airbnb, created in 2007 in San Francisco and which in 2009 assumed the current denomination. Airbnb operates in 200 countries and about 8.100 cities, launching 5 million announcements yearly and hosting – through its associated structures – about 300 million people per year (Rubino, 2018), having reached in 2018 the target of 500 million people (AIRBNB, 2019).